Dangerous Memories and Violence - Donald Tyoapine Komboh (Religions)
The big challenge regarding social violence is relationships and the quest for societies to live together. As a result, this has affected, in different ways, how various demographics are composed, economies are built and religions are practiced. This investigation weighs in on these matters to delineate the issues critically. It spotlights the thrust of the matter, which is based on trust and fairness. Adopting a categorical theological method, this article interrogates Johann Baptist Metz’s categories of memory, solidarity and narratives in reverse. It highlights relationships, narratives and community to dissect the issues of violence in Taraba State with the intention of restoring relationships. Conflicts result from a series of broken relationships, and they become ethnic and religious. In intentionally engaging these categories, the hope is that they serve as a formidable resource for interrogating these conflicts and providing a reset for healthy living.